Days of blood & starlight eaudiobook - Taylor, Laini (Daughter of Smoke & Bone, 2013)
An art student and monster's apprentice must decide how far she'll go to avenge her people in this riveting sequel to the mesmerizing, acclaimed book Daughter of Smoke & Bone by National Book Award finalist Laini Taylor — now with a gorgeous new package! Once upon a time, an angel and a devil fell in love and dared to imagine a world free of bloodshed and war. This is not that world. Art student and monster's apprentice Karou finally has the answers she has always sought. She knows who she is — and what she is. But with this knowledge comes another truth she would give anything to undo: She loved the enemy and he betrayed her, and a world suffered for it. In this stunning sequel to the highly acclaimed Daughter of Smoke & Bone , Karou must decide how far she'll go to avenge her people. Filled with heartbreak and beauty, secrets and impossible choices, Days of Blood & Starlight finds Karou and Akiva on opposing sides as an age-old war stirs back to life. While Karou and her allies build a monstrous army in a land of dust and starlight, Akiva wages a different sort of battle: a battle for redemption. For hope . But can any hope be salvaged from the ashes of their broken dream?